Korelasi Karakteristik pasien Terhadap Penerimaan Diagnosa Kanker Payudara - Rahmiwati, Rahmiwati (REAL in Nursing Journal, 2020)
Background : Cancer diagnosis is often a stressor for sufferers, especially if you have to undergo cancer treatment such as chemotherapy. The effects of these negative thoughts can cause problems both physically and psychologically which can worsen the patient's condition. Methods: The questionnaire used to see the Acceptance Of Illness Scale (AIS). The number of samples is 180 patients. Data analysis: proportion, chi square. Results: The results showed that 60.6% of the patients admitted to the West Sumatra Provincial Hospital were good. While the factors that affect the quality of life of patients are: Age (p = 0.006), education (p = 0.902), occupation (p = 0.006). Conclusion: Patient acceptance can be increased by optimizing the factors possessed by breast cancer sufferers. Suggestion: Further research on job variables is explained based on professional status.Keywords: Breast Cancer, Acceptance Stage, Acceptance Of Illness